CHEMICAL COMPOSITIONS OF CARBONATE MINERALS FROM BAYAN OBO, INNER MONGOLIA, CHINA: IMPLICATIONS FOR PETROGENESIS - Yang X.-M.; Le Bas M.J. (My University, 2004)
Carbonate rocks at the Bayan Obo giant rare earth element (REE)–Nb–Fe ore deposit, Inner Mongolia, China are divided into four categories: sedimentary limestone and dolostone (H8s), deformed mineralized coarse-grained dolomite marble (H8c) and fine-grained dolomite marble (H8f), and carbonatite dikes (D), based on their texture, mineral assemblage and geological occurrence. Although the sedimentary carbonate rocks (H8s) show weak deformation north of the Kuangou fault zone, this unit is not metamorphosed, which occurs together with quartz sandstone, sandstone and shale, comprising the Middle Proterozoic Bayan Obo Group. In contrast, the mineralized fine-to-coarse-grained dolomitic marbles (H8f and H8c) that occur to the south of the Kuangou fault zone are sheared, deformed and metamorphosed. The H8c consist mainly of dolomite associated with apatite, magnetite, minor pyrochlore, and sodic amphibole. Dolomite in the main ore-bearing unit (H8f) occurs with magnetite, monazite, bastnaesite, and parisite. Fine-grained monazite occurs as fracture fillings in dolomite. Electron microprobe data show that dolomite and/or ankerite in the ore-bearing rocks (H8c and H8f) are similar to carbonatite dikes (D) occurring within 3.5 km northeast of the deposit. These carbonates contain high MnO (>0.50 wt.%) and SrO (>0.15 wt.%) as is typical of carbonatites; this contrasts with very low MnO and SrO (<0.1 wt.%) in typical sedimentary limestone and dolostone (H8s). The variation of MnO and SrO content in dolomite from the ore-bearing dolomite marbles may be interpreted by fractional crystallization of a carbonatitic magma, which results in REE enrichment in the evolved residual magma. This interpretation is consistent with their field relations, trace element geochemistry, stable isotopes, and 87Sr/86Sr ratios. The MnO and SrO contents of carbonate minerals may be used as important chemical characteristics to identify their genesis. MnO and SrO contents in carbonate minerals higher than 0.15 wt.% are used as indicators to distinguish carbonatite from sedimentary carbonate rocks. These criteria together with fenitization may be taken as critical signatures to separate carbonatites from sedimentary carbonate rocks, even when both were metamorphosed to marbles.
Keywords: Carbonate minerals; Dolomite; Dolomite marble; Carbonatite; Bayan Obo